Management of Childhood Headache in the Emergency Department. Review of the Literature - Raucci, Umberto; Della Vecchia, Nicoletta; Ossella, Chiara; Paolino, Maria Chiara; Villa, Maria Pia; Reale, Antonino; Parisi, Pasquale (Frontiers in Neurology, 2019)
Headache is the third leading cause of referral to pediatric emergency departments (ED). Based on a systematic review, headaches in children evaluated in the ED are primarily due to benign conditions that tend to be self-limiting or resolve with appropriate pharmacological treatment. The causes of non-traumatic headache in the ED include more frequently primitive headaches (21.8-66.3%) and benign secondary headaches (35.4-63.2%), whereas potentially life-threatening (LT) secondary headaches are less frequent (2 to 15.3%). Worrying conditions include brain tumors, central nervous system infections, dysfunction of ventriculo-peritoneal shunts, hydrocephalus, idiopathic intracranial hypertension and intracranial hemorrhage. In the emergency setting, the main goal is to intercept potentially LT conditions that require immediate medical attention. The initial assessment begins with an in-depth, appropriate history followed by a complete, oriented physical and neurological examination. The literature describes the following red flags requiring further investigation (for example neuroimaging) for recognition of LT conditions: abnormal neurological examination; atypical presentation of headaches: subjective vertigo, intractable vomiting or headaches that wake the child from sleep; recent and progressive severe headache (<6 months); age of the child <6 years; no family history of migraine or primary headache; occipital headache; change in the type of headache; new headache in an immunosuppressed child; first or worse headache; systemic symptoms and signs; headaches associated with changes in mental status or focal neurological disorders. In evaluating a child or adolescent who is being treated for headache, physicians should consider using appropriate diagnostic tests. Diagnostic tests are varied, including routine laboratory analysis, cerebral spinal fluid examination, electroencephalography and neuroimaging with computerized tomography or magnetic resonance imaging . The management of headache in the ED depends on the general clinical condition of the patient and the presumable etiology of the headache. Despite the pharmacological options for the management of acute migraine, few randomized controlled trials exist in the pediatric population. Composite data demonstrate that only ibuprofen and sumatriptan are significantly more effective than placebo in determining headache relief in children.